Pythagoras on the rocks. A proof with bricks - Michele Cagol; Alessandro Efrem Colombi (Firenze University Press, 2016)
In this short paper a practical and simple proof of the Pythagorean theorem is proposed. It uses colourful interlocking plastic bricks with two shapes: a cube that measures two centimeters on each side and a right prism where the base is a right-angled isosceles triangle and the two equal rectangular faces are the same as those of the cubic brick. The proof is designed for primary school children (but also for preschool children) and begins by telling the legend of Pythagoras, who discovered his theorem by looking at the floor tile pattern of Polycrates' palace. This proof takes into account only right-angled isosceles triangle but it is possible to show the validity of Pythagorean theorem for all right-angled triangles by building a simple proof by rearrangement.   Pitagora on the rocks. Una dimostrazione con i mattoncini In questo breve contributo viene proposta una semplice dimostrazione pratica del teorema di Pitagora, utilizzando mattoncini a incastro di plastica colorata di due forme: un cubo di due centimetri per lato e un prisma retto la cui base è un triangolo isoscele rettangolo e nel quale le due facce equivalenti sono uguali a quelle del mattoncino cubico. La dimostrazione è rivolta a bambini della scuola primaria (ma, eventualmente, anche in età prescolare) e prende le mosse dalla leggenda secondo la quale Pitagora avrebbe scoperto il suo teorema mentre stava osservando il pavimento piastrellato del palazzo di Policrate, tiranno di Samo. Da questa dimostrazione - che prende in considerazione solo triangoli rettangoli isosceli - è poi possibile passare a una dimostrazione del teorema di Pitagora per tutti i triangoli rettangoli.